2020
DOI: 10.1002/ehf2.12641
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxygen uptake kinetics after exercise caused by differences in loading pattern and exercise intensity

Abstract: Aims The kinetics of recovery-period oxygen uptake (VO 2 ) are affected by the O 2 deficit generated during exercise. However, studies using ramp tests (RTs) and constant work rate tests (CT) have differently characterized VO 2 responses to increased exercise intensity differently. We used these two types of loading patterns to investigate the effects of low-intensity, mediumintensity, and high-intensity exercises on the half time (T 1/2 ) of recovery-period VO 2 and the mechanism. Methods and results Ten heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A recent study showed that the level of exhaustion had no impact on V̇O 2 off-kinetics ( Ichikawa et al, 2020 ). That the determination of V̇O 2 -kinetics, unlike V̇O 2peak , does not require the subject to perform the test to maximal voluntary exertion is a large advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the level of exhaustion had no impact on V̇O 2 off-kinetics ( Ichikawa et al, 2020 ). That the determination of V̇O 2 -kinetics, unlike V̇O 2peak , does not require the subject to perform the test to maximal voluntary exertion is a large advantage.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of rel V̇O 2 reduction 60 s post-test (%) or slope linear V̇O 2 off-kinetics (ml/min/s) is recommended to distinguish between healthy individuals and patients with HF. Since V̇O 2 off-kinetics is not affected by the level of exhaustion ( Ichikawa et al, 2020 ), these parameters might be used as a substitute for V̇O 2peak when maximal exhaustion is not reached or when V̇O 2peak cannot be interpreted.…”
Section: Discussionmentioning
confidence: 99%